IDENTIFICATION AND DIFFERENTIATION OF POULTRY MEAT AND PRODUCTS USING PCR-RFLP TECHNIQUE - Kamaran Taha; Dilger Khdr; Karwan Kareem (Mesopotamia Journal of Agriculture)
The mitochondrial cyt b gene plays a serious role in investigating untruthful meat species. This study aimed to authenticate the species of poultry products (Escallop, Nugget, Steak, and Sausage) depending on cyt b gene by using universal cyt b primer. DNA was isolated, and then a band of 359 bp of a mitochondrial cytochrome b gene was produced during the PCR amplification. The PCR products were exposed to Hinf1 and Rsa I restriction enzymes. The restricted fragments produced by the restriction fragment length polymorphism technique (RFLP), were run by agarose gel electrophoresis. Results showed that all products had a similar band except sausage product does not follow the rule and showed mislabeling product by the REs, Two bands were yielded by HinfI RE for all products (114 and 245) bp with the differentiated sausage among other products based on the fake product (63 and 296) bp, while digestion by Rsa I produced three bands for escallop, nugget, and steak, (63, 100, 196), but only two bands for sausage was generated (148 and 211). As result, the study offered that analyzing meat products to detect the origin species via a PCR-RFLP technique by using these restriction enzymes can give reliable results. In short susage is considered as a frau product because the results showed different bands as compaired with poultry meat.